Management: a competency based approach - Hellriegel, Don; Jackson, Susan E.; Slocum, Jr., John W. (Australia : Tomson south-western, 2005)
Business
Keywords: Management; Management; Managerial Competencies; Evolution of management; planning and administration competency; Environment managing; Global Economy Entrepreneurship; Planning and Control; Planning and Strategy; Decision Making; decision Aids; Waste management restores; Organizational Design Organizational Change; Teamwork competency; Managing Human Resources; Training and Development; Leading; Organizational Communication; Cultural Diversity